Acute primary angle-closure in Sturge-Weber syndrome - Wei-Wen Su (American Journal of Ophthalmology Case Reports, 2018)
Purpose: Sturge-Weber syndrome (SWS) is a neurocutaneous disorder characterized by facial cutaneous venous dilatation (port-wine stain), leptomeningeal angioma, and ocular abnormalities. Here we report a case of SWS who experienced acute primary angle-closure in the same side of the nevus flammeus. Observations: A 64-years-old female patient with SWS port wine stain on the left side of her face was referred to our ER for acute primary angle-closure (PAC). The IOP was 64 mmHg in the left eye (12 mmHg in OD) and the visual acuity was 20/100. The acute PAC was aborted after medical treatment with intravenous Mannitol and oral Acetazolamide, but laser iridotomy (LI) was not performed because of the risk of bleeding. After the acute episode, her IOP remained stable in midteen under 3 topical medications. However, the patient reported several subacute attacks in the following month. We arranged phacoemulsification and intraocular lens (IOL) implantation two months after the initial PAC attack. The post-op condition was smooth with 20/20 visual acuity, and the angle opened dramatically on anterior segment optical coherence tomography (AS-OCT). Her IOP was around 13 mmHg without medication and there was no more acute PAC attack. Conclusions: SWS with ipsilateral acute PAC has seldom been reported. Lens extraction and IOL implantation can be an option in treating such patients since conventional laser iridotomy may cause bleeding. Keywords: Sturge-Weber syndrome, Acute primary angle-closure glaucoma, Phacoemulsification, Intra-ocular lens implantation, Laser iridotomy